Inhibition of LPS-induced inflammation and signaling pathways in fallopian tube epithelial cells by estrogen and progesterone - Qianqian Li; Jianqi Liu; Bayaer Nashun; Sarina Bai; Xiaozhen Guo; Ling Wu; Tuya Bao (BMC Veterinary Research)
Abstract Aim The inhibitory effects of estrogen and progesterone on lipopolysaccharide (LPS)-induced inflammation and the nuclear factor-κB (NF-κB), mitogen-activated protein kinase (MAPK), and phosphoinositide-3 kinase (PI3K)/protein kinase B (Akt) signaling pathways in mouse oviductal epithelial cells were investigated. Methods Mouse oviduct epithelial cells were isolated for various in vitro experiments. The CCK-8 method was used to detect the effects of LPS, LPS + Dexamethasone (DXM), LPS + E2, and LPS + P4 on the viability of fallopian tube epithelial cells. RT‒qPCR was used to measure the expression levels of IL-1β, TNF-α, IL-10, and β-defensin-2 (mBD-2) in cells. ELISA was used to measure the levels of IL-1β in cells. Western blotting was used to detect the protein expression of NF-κB p65, IκBα, p38, P-p38, Akt, and P-Akt in cells. Additionally, a salpingitis mouse model was constructed with LPS, and the model mice were treated with estrogen (E2), progesterone (P4), and DXM. The ovarian tissues were collected and subjected to HE staining. Moreover, IL-10 and mBD-2 expression in the tissue was detected by immunohistochemical staining. Key findings Estrogen and progesterone significantly inhibited the production of IL-1β, TNF-α, IL-10, and mBD-2, thereby effectively suppressing the inflammatory response induced by LPS. In terms of signaling pathways, estrogen and progesterone significantly inhibited the protein expression of NF-κB, MAPK, and PI3K/Akt pathway members induced by LPS. Significance Estrogen and progesterone can protect against LPS-induced mouse salpingitis by inhibiting the activation of the NF-κB, MAPK, and PI3K/Akt signaling pathways and suppressing the expression of the inflammatory factors IL-1β, TNF-α, IL-10, and mBD-2. Brief Summary Estrogen and progesterone can effectively reduce the inflammatory response of the fallopian tubes. Strengths and limitations of this study The advantages of this study are as follows: high data reliability; a large number of experimental repetitions, resulting in stable outcomes; and a concise and efficient explanation of the issues. Limitation The research objective is too broad.